Improved methodology determining the probability of fire damage to the enemy object, taking into account its resistance - Oliinyk, Volodymyr (Social Development and Security, 2021)
Technological development of the warring parties, the introduction of new forms and methods of armed struggle, the trend of transition to a network-centric war necessitate the search for new approaches to evaluating the effectiveness of units in carrying out combat tasks. The combat effectiveness will largely depend on a detailed assessment of the capabilities of the available weapons of the warring parties. Therefore, the improved methodology for determining the probability of firing by the unit is based on the most acceptable algorithm based on probability theory. The proposed partial methodology, based on known methods for determining the probability of firing, the number of weapons samples and their tactical and technical characteristics, allow to determine the number of successful shots fired by the warring parties during the battle. Taking into account the conditions specified in the improved methodology, the probability of firing the enemy target by the unit is determined, taking into account its counteraction. The practical value of the improved methodology is to enable the unit commander to adjust his decision taking into account the assessment of the effectiveness of the firing means at his disposal. At the same time, the improved methodology can be a part of the mathematical model of the targeted unit against enemy targets, which is based on the method of two functions.